Low‐T CO Oxidation over Cu−CHA Catalysts in Presence of NH3: Probing the Mobility of CuII Ions and the Role of Multinuclear CuII Species. Issue 15 (29th June 2020) - Villamaina, Roberta; Iacobone, Umberto; Nova, Isabella; Ruggeri, Maria Pia; Collier, Jillian; Thompsett, David; Tronconi, Enrico
Abstract : The Cover Feature portrays two Cu II ions as trapeze artists swinging inside a CHA zeolite cage until they join hands to form a single complex. In their Communication, reporting CO titration experiments over preoxidized Cu‐CHA catalysts, R. Villamaina et al. provide evidence that NH3 ligands, like trapezes, mobilize initially isolated Cu II ions to form the dimeric complexes with removable oxygen needed for CO oxidation. This is confirmed by transient kinetic analysis, which shows that the rate of Cu II reduction is 2 nd order in the ZCu II OH species. These findings may be relevant for elucidation of the reduction half cycle in the redox mechanism of the Standard NH3 ‐SCR reaction over Cu‐CHA systems. More information can be found in the Communication by R. Villamaina et al .